2009
DOI: 10.2215/cjn.03930808
|View full text |Cite
|
Sign up to set email alerts
|

Progression of Coronary Artery Calcification in Renal Transplantation and the Role of Secondary Hyperparathyroidism and Inflammation

Abstract: Background and objectives: Transplantation should favorably affect coronary calcification (CAC) progression in dialysis; however, changes in CAC score in the individual patient are not reliably evaluated.Design, setting, participants & measurements: The authors used special tables of reproducibility limits for each score level to study, by multislice computed tomography and biochemistries, the 2-year changes in CAC in 41 transplant patients (age 48 ؎ 13 yr, 25 men, dialysis vintage 4.8 ؎ 4.3 yr, underwent tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
79
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(86 citation statements)
references
References 27 publications
5
79
1
1
Order By: Relevance
“…That a higher baseline CAC score is associated with CAC progression confirms previous studies both in RTR (14) and in hemodialysis patients (13). Studies in dialysis patients as well as in renal transplant recipients have demonstrated the strong association of CVE history with CAC, the latter most likely related to atherosclerosis (23,24,25,19) (30).…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…That a higher baseline CAC score is associated with CAC progression confirms previous studies both in RTR (14) and in hemodialysis patients (13). Studies in dialysis patients as well as in renal transplant recipients have demonstrated the strong association of CVE history with CAC, the latter most likely related to atherosclerosis (23,24,25,19) (30).…”
Section: Discussionsupporting
confidence: 84%
“…Interestingly, the score increased in the dialysis group whereas it remained stable in RTR. The relatively small size of this study and limited duration of follow-up very likely accounts for the discrepancy with our results (13). The other 3 series were in incident RTR.…”
Section: Discussioncontrasting
confidence: 74%
See 2 more Smart Citations
“…3,4 The ensuing hypercalcemia can lead to interstitial calcification in the allograft with graft dysfunction 5,6 and soft tissue calcification. 7,8 Primary hyperparathyroidism (pHPT) 9,10 and sHPT 11,12 are both associated with abnormalities in glucose metabolism, such as glucose intolerance and insufficient insulin release. Furthermore, a higher prevalence of diabetes mellitus (DM) has been reported in patients with pHPT.…”
Section: Introductionmentioning
confidence: 99%